Implementation of Economic Crime After The Provision of Law Number 11 of 2021 Concerning The Prosecutor - Supardi . (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2022)
The Criminalization of Economic Crimes occurred on May 11, 1995 which was marked by the birth of the Law on Economic Crimes (UUTPE). Since the birth of the law, the term "harming the economy" has emerged, which is similar to the element "harming the country's economy" in the Corruption Crime (TPK) offense. On December 31, 2021, the Prosecutor's Law (UUK) was promulgated which gives authority to investigate, investigate and prosecute cases of Economic Crimes (TPE), but in the explanation of Article 35 paragraph (1) letter k provides an interpretation of economic crimes such as the interpretation of "harmful" the country's economy” in the TPK. The use of the phrase "harming the country's economy" in the explanation of Article 35 paragraph (1) letter k of the UUK raises interpretation problems regarding the meaning of "harming the economy" as referred to in the UUPE which can have an impact on implementation in creating justice and legal certainty in handling TPE cases. Therefore, this study formulated the formulation of the problem as follows: (1) How to interpret the TPE regulated in the UUTPE (2) How to distinguish the TPE regulated in the UUTPE and UUTPK and (3) How to measure the authority of the Prosecutor's Office in handling TPE cases so as to create justice and legal certainty. The research method used is normative juridical, namely a method that refers to the applicable laws or regulations, legal theories or opinions of scholars. The research is based on secondary data, while the research specifications used are descriptive analytical. The data sources used consist of primary legal materials and secondary legal materials. The results of the study conclude that: (1) UUTPE has not been revoked and is still valid as ius constitutum, (2) The basic differences in the state economy between UUTPE and UUTPK are: TPE is more related to the world of trade and is not related to strategic policies of the central or regional government and (3) Based on Law Number 11 of 2021 concerning Amendments to Law Number 16 of 2004 the Prosecutor's Office has the authority to handle TPE cases, but the definition of the state economy according to the law is still confusing because it is equated with the meaning in the UUTPK